Secondary battery and method of manufacturing the same

KR1020260153152APending Publication Date: 2026-10-21TOYOTA JIDOSHA KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020260066249
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-04-14
Filing Date
2026-04-13
Publication Date
2026-10-21

Smart Images

  • Figure P1020260066249_ABST
    Figure P1020260066249_ABST
Patent Text Reader

Abstract

[Project] Provides a highly durable secondary battery. [Solution] A positive electrode and a negative electrode are positioned opposite each other with a separator in between. The negative electrode comprises a negative electrode current collector, a negative electrode composite layer containing graphite particles provided on the negative electrode current collector, and an adhesive layer provided between the surface of the negative electrode composite layer and the separator. The negative electrode composite layer comprises a surface layer in contact with the adhesive layer and a main layer located between the surface layer and the negative electrode current collector. In the XRD profile of the main layer, the degree of orientation, which is the intensity ratio obtained by dividing the intensity of the (110) plane of the graphite crystal by the intensity of the (002) plane, is 0.03 or greater. The particle size distribution of the graphite particles included in the surface layer has a first particle size and a second particle size smaller than the first particle size. The particle size distribution of the graphite particles included in the main layer has a peak at the first particle size and does not have a peak at the second particle size.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The technology disclosed in this specification relates to a secondary battery and a method for manufacturing a secondary battery. Background Technology

[0002] The negative electrode used in a secondary battery comprises a conductive negative electrode current collector and a negative electrode composite layer provided on the negative electrode current collector. The negative electrode composite layer contains graphite particles having a layered crystal structure. The charging and discharging function is realized by the absorption and release of metal ions between the layers of graphite particles. Accordingly, a technique has been proposed to orient the layer planes of the graphite particles approximately perpendicular to the negative electrode current collector by utilizing the magnetic field orientation of the graphite particles (e.g., Patent Document 1). The closer the layer planes of the graphite particles are to being perpendicular to the negative electrode current collector, the more smoothly the absorption and release of metal ions between the layers of the graphite particles can be performed. Therefore, it is possible to improve the performance of the secondary battery. Prior art literature

[0003] Japanese Patent Publication No. 2024-85026 The problem to be solved

[0004] The surface layer of the negative electrode composite layer and the separator are bonded together via an adhesive layer. As described above, when the graphite particles included in the negative electrode composite layer are magnetically oriented, the angle formed between the layer plane of the graphite particles and the surface of the negative electrode current collector becomes larger. Consequently, the surface roughness of the surface layer of the negative electrode composite layer increases when magnetically oriented compared to when it is not. As a result, there is a risk that the adhesion between the surface layer of the negative electrode composite layer and the separator will deteriorate. means of solving the problem

[0005] The technology disclosed in this specification is implemented in a secondary battery. A first aspect of the technology is a secondary battery in which a positive electrode and a negative electrode face each other with a separator interposed therebetween. The negative electrode comprises a negative electrode current collector, a negative electrode composite layer provided on the negative electrode current collector and containing graphite particles, and an adhesive layer provided between the surface of the negative electrode composite layer and the separator. The negative electrode composite layer comprises a surface layer in contact with the adhesive layer and a main layer located between the surface layer and the negative electrode current collector. In the XRD profile of the main layer, the degree of orientation, which is the intensity ratio obtained by dividing the intensity of the (110) plane of the graphite crystal by the intensity of the (002) plane, is 0.03 or greater. The particle size distribution of the graphite particles included in the surface layer has a first particle size and a second particle size smaller than the first particle size. The particle size distribution of the graphite particles included in the main layer has a peak at the first particle size and does not have a peak at the second particle size.

[0006] According to the above structure, the particle size distribution of graphite particles included in the surface layer has a peak at the first particle size, in addition to having a peak at the second particle size, which is smaller than the first particle size. That is, in the surface layer, there exists a group of particles having the first particle size and a group of particles having the second particle size. Accordingly, it is possible to create a state in which particles having the second particle size are filled in the gaps between particles having the first particle size. By filling the concave areas between particles having the first particle size with particles having the second particle size, the surface roughness of the surface layer can be reduced. Therefore, it becomes possible to increase the adhesion between the surface layer of the negative electrode composite layer and the separator. Brief explanation of the drawing

[0007] Figure 1 is a perspective view of a secondary battery (1). Figure 2 is an exploded plan view of the electrode body (108). Figure 3 is a cross-sectional view of the negative electrode (114). Figure 4 is the measurement result of the particle size distribution of the surface layer (10A). Figure 5 is the measurement result of the particle size distribution of the main layer (10B). FIG. 6 is a flowchart describing the method of manufacturing a secondary battery (1). Figure 7 is a figure illustrating an example of the preparation process of the first paste. Figure 8 is a diagram illustrating steps S20-S50. Figure 9 is a diagram illustrating steps S100 and S110. Figure 10 is a diagram illustrating the heating press process. Figure 11 is a cross-sectional view of the negative electrode of the first comparative example. FIG. 12 is a cross-sectional view of the negative electrode of the second comparative example. Specific details for implementing the invention

[0008] In the second embodiment of the present technology, in addition to the first embodiment above, the particle size distribution of graphite particles on the surface of the negative electrode composite layer may have peaks at the first particle size and the second particle size.

[0009] According to the above configuration, on the surface of the negative electrode composite layer, the concave portions between particles having a first particle size can be filled with particles having a second particle size. The surface roughness of the negative electrode composite layer can be reduced.

[0010] The technology disclosed in this specification is implemented as a method for manufacturing a secondary battery. A third aspect of the technology is a method for manufacturing a secondary battery in which a positive electrode and a negative electrode face each other via a separator. The manufacturing method comprises a first coating process in which a first paste containing first graphite particles having a peak at a first particle size is coated onto the surface of a negative electrode current collector to form a first layer. The manufacturing method comprises a second coating process in which a second paste containing second graphite particles having a peak at a second particle size smaller than the first particle size is coated onto the surface of the first layer to form a second layer. The manufacturing method comprises a magnetic field alignment process in which an external magnetic field is applied to the first layer and the second layer. The manufacturing method comprises a drying process in which the first layer and the second layer are dried after the magnetic field alignment process.

[0011] According to the above configuration, the first layer (L1) and the second layer (L2) can be magnetically oriented while in a fluid state. The second graphite particles can be moved to be introduced into the concave portion formed by the magnetic orientation of the first graphite particles. This makes it possible to reduce surface roughness.

[0012] In the fourth embodiment of the present technology, in addition to the third embodiment above, the particle size distribution of graphite particles on the surface of the second layer after the drying process may have peaks at the first particle size and the second particle size.

[0013] According to the above configuration, on the surface of the second layer, the concave portions between particles having a first particle size can be filled with particles having a second particle size. The surface roughness of the second layer can be reduced.

[0014] In the fifth embodiment of the present technology, in addition to the third or fourth embodiment above, the median diameter of the first graphite particle may be larger than the median diameter of the second graphite particle.

[0015] In the sixth embodiment of the present technology, in addition to the fifth embodiment above, the median diameter of the first graphite particle may be within the range of 15 to 40 micrometers. The median diameter of the second graphite particle may be within the range of 5 to 20 micrometers.

[0016] [Example]

[0017] Structure of the secondary battery (1)

[0018] FIG. 1 shows a perspective view of a secondary battery (1) related to the present embodiment. In the present embodiment, as one of the preferred embodiments of the secondary battery (1), it is described by embodying it as a lithium-ion secondary battery. As shown in FIG. 1, the secondary battery (1) comprises a housing (102), a positive electrode terminal (104), a negative electrode terminal (106), an electrode body (108), and a non-aqueous electrolyte (110). The housing (102) accommodates the electrode body (108) and the non-aqueous electrolyte (110). The housing (102) comprises a housing body (102a) and a cover plate (102b). The housing body (102a) is a box body having an opening (102c) at the top. The cover plate (102b) is mounted on the opening (102c) and blocks the opening (102c).

[0019] Each of the positive terminal (104) and the negative terminal (106) is mounted on a cover plate (102b). One end (104a) of the positive terminal (104) is exposed to the outside of the housing (102). The other end (104b) of the positive terminal (104) is connected to the positive connection part (112a) of the electrode body (108) inside the housing (102). One end (106a) of the negative terminal (106) is exposed to the outside of the housing (102). The other end (106b) of the negative terminal (106) is connected to the negative connection part (114a) of the electrode body (108) inside the housing (102).

[0020] FIG. 2 shows an exploded plan view of an electrode body (108). The electrode body (108) is provided with a positive electrode (112), a negative electrode (114), and a separator (116). Each of the positive electrode (112), the negative electrode (114), and the separator (116) is in the shape of a long sheet. The positive electrode (112) and the negative electrode (114) are stacked with the separator (116) interposed. The electrode body (108) is formed by winding the stack of the positive electrode (112) and the negative electrode (114). However, the electrode body (108) does not necessarily have to be a wound electrode body. The electrode body (108) may be, for example, a so-called stacked electrode body in which a plurality of positive electrodes (112) and a plurality of negative electrodes (114) are alternately stacked with the separator (116) interposed.

[0021] The positive electrode (112) is provided with a positive electrode current collector (118) and a positive electrode active material sheet (120). The positive electrode current collector (118) is a conductive sheet. The positive electrode current collector (118) is, for example, an aluminum foil. The positive electrode active material sheet (120) is disposed on the surface of the positive electrode current collector (118). The positive electrode active material sheet (120) is provided with a positive electrode active material. As a positive electrode active material, for example, a lithium composite oxide may be provided. On one side edge in the width direction of the positive electrode (112), a positive electrode exposed portion (118a) is provided in which the positive electrode current collector (118) is exposed. The positive electrode exposed portion (118a) forms a positive electrode connection portion (112a) by being wound and overlapped when forming the electrode body (108).

[0022] The negative electrode (114) is provided with a negative electrode current collector (122) and a negative electrode composite layer (10). The negative electrode current collector (122) is a conductive sheet. The negative electrode current collector (122) is, for example, a copper foil. The negative electrode composite layer (10) is disposed on the surface of the negative electrode current collector (122). Specific details regarding the negative electrode (114) will be described later. On one side edge in the width direction of the negative electrode (114), a negative electrode exposure portion (122a) is provided in which the negative electrode current collector (122) is exposed. When forming the electrode body (108), the negative electrode exposure portion (122a) is wound and overlapped to form a negative electrode connection portion (114a).

[0023] The separator (116) is configured to allow a charge carrier (here, lithium ions) to pass through. Examples of separators (116) include porous polymer membranes such as porous polyethylene membranes, porous polypropylene membranes, porous polyolefin membranes, and porous polyvinyl chloride membranes, as well as lithium ion conductive polymer electrolyte membranes. These separators (116) may be used alone or in combination with multiple types.

[0024] The non-aqueous electrolyte (110) penetrates into the interior of the electrode body (108). The non-aqueous electrolyte (110) includes a non-aqueous solvent and a supporting salt. Examples of non-aqueous solvents include carbonates, ethers, esters, nitriles, sulfones, and lactones. Additionally, examples of supporting salts include lithium salts containing fluorine. Each of the non-aqueous solvent and the supporting salt may be composed of a single type of material or a plurality of types of materials.

[0025] Structure of the negative pole (114)

[0026] FIG. 3 shows a cross-sectional view of the negative electrode (114). FIG. 3 also shows a separator (116). In FIG. 3, the direction parallel to the negative electrode current collector (122) is defined as the x and y directions. Also, the direction perpendicular to the negative electrode current collector (122) (the thickness direction of the negative electrode (114)) is defined as the z direction. Additionally, for the purpose of clarity in illustration, only one of the components arranged in multiple places may be labeled. The same applies to subsequent drawings. The negative electrode (114) mainly comprises a negative electrode current collector (122), a negative electrode composite layer (10), and an adhesive layer (13).

[0027] The adhesive layer (13) is provided between the surface (10s) of the negative electrode composite layer (10) and the separator (116), and the two are bonded together. The adhesive layer (13) is a layer containing resin particles. In FIG. 3, the resin particles constituting the adhesive layer (13) are similarly represented by white circles. The composition of the adhesive layer (13) may vary. In addition, the composition of the adhesive layer (13) may be the same as the composition of the binder (14) described later. In this embodiment, the adhesive layer (13) is made of PVdF, which is the same as the binder (14).

[0028] The negative electrode composite layer (10) is provided on the negative electrode current collector (122). The negative electrode composite layer (10) comprises graphite particles (11), a binder (14), and a conductive agent not shown. For the graphite particles (11), a graphite-based carbon material such as natural graphite, artificial graphite, or an amorphous form thereof may be used. For example, the graphite particles (11) may be flat, flaky graphite, or spheroidized graphite formed by spheroidizing flaky graphite. In this embodiment, flaky graphite is used as the graphite particles (11). This is because flaky graphite is flat and can be stably oriented by applying a magnetic field.

[0029] The binder (14) is a component for binding graphite particles (11) together. The binder (14) is mixed into the negative electrode composite layer (10). The binder (14) contains a resin in the form of particles. In FIG. 3, the binder (14) is similarly represented by a white circle. Examples of binders (14) include polyvinylidene fluoride (PVdF), various acrylic resins, carboxymethylcellulose (CMC), styrene butadiene rubber (SBR), polytetrafluoroethylene (PTFE), etc. As an acrylic resin, a homopolymer obtained by polymerizing monomers such as acrylic acid, methacrylic acid, acrylamide, methacrylamide, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, methacrylate, methyl methacrylate, ethylhexyl acrylate, and butyl acrylate into one type may be used. Additionally, the acrylic resin may be a copolymer obtained by polymerizing two or more of the above monomers. The binder (14) may be composed of a single type of material or may be composed of multiple types of materials. In this embodiment, the binder (14) is PVdF.

[0030] The negative electrode composite layer (10) has a surface layer (10A) and a main layer (10B). The surface layer (10A) is a layer in contact with the adhesive layer (13). The main layer (10B) is a layer located between the surface layer (10A) and the negative electrode current collector (122). The main layer (10B) is a layer mainly composed of first graphite particles (11_1). In FIG. 3, the first graphite particles (11_1) are shown as hatching. The surface layer (10A) is a layer composed of second graphite particles (11_2) in addition to the first graphite particles (11_1). In FIG. 3, the second graphite particles (11_2) are shown painted gray.

[0031] The median diameter of the first graphite particle (11_1) is larger than the median diameter of the second graphite particle (11_2). The median diameter of the first graphite particle (11_1) is, for example, within the range of 15 to 40 micrometers. The median diameter of the second graphite particle (11_2) is, for example, within the range of 5 to 20 micrometers. Furthermore, the median diameter referred to here means the particle diameter (D50) at 50% of the cumulative value in the volume-based particle size distribution measured by the laser diffraction and scattering method. In this embodiment, the median diameter of the first graphite particle (11_1) was set to 20 micrometers. Also, the median diameter of the second graphite particle (11_2) was set to 10 micrometers.

[0032] FIG. 4 shows the measurement results of the particle size distribution of the surface layer (10A). FIG. 5 shows the measurement results of the particle size distribution of the main layer (10B). FIG. 4 and FIG. 5 are volume-based particle size distributions measured by laser diffraction and scattering methods. The horizontal axis of FIG. 4 and FIG. 5 is the particle diameter, and the vertical axis is the volume percentage. As shown in FIG. 4, the particle size distribution of the surface layer (10A) has peaks (modes) at the first particle diameter (P1) and the second particle diameter (P2). This is because the surface layer (10A) contains both the first graphite particle (11_1) and the second graphite particle (11_2). In the example of FIG. 4, the first particle diameter (P1) is about 20 micrometers, and the second particle diameter (P2) is about 10 micrometers. Meanwhile, as shown in FIG. 5, the particle size distribution of the main layer (10B) has a peak at the first particle size (P1) and does not have a peak at the second particle size (P2). This is because the main layer (10B) is a layer that mainly contains first graphite particles (11_1).

[0033] Based on the above, it can be seen that the surface layer (10A) and the main layer (10B) can be distinguished depending on whether the particle size distribution has peaks at the first particle size (P1) and the second particle size (P2). That is, it is possible to define the boundary between the surface layer (10A) and the main layer (10B) by the particle size distribution.

[0034] In addition, a surface layer (10A) is exposed on the surface (10s) of the negative electrode composite layer (10). Accordingly, the measurement result of the particle size distribution on the surface (10s) has peaks at the first particle size (P1) and the second particle size (P2), as shown in FIG. 4.

[0035] Orientation of graphite particles

[0036] As described above, the graphite particle (11) is flat, flake-like graphite. The flake-like graphite is composed of a number of stacked plate-shaped (graphene) structures having hexagonal crystals. Therefore, the graphite particle (11) has a roughly plate-like shape. The graphite particle (11) has a (002) plane and a (110) plane. The (002) plane is a layer plane (a plane horizontal to the graphite layer) of the layered graphite particle. The (002) plane is a plane horizontal to the carbon network of the graphene sheet constituting the graphite particle (11). The (110) plane is a cross-section (a plane perpendicular to the graphite layer) of the layered graphite particle. The (110) plane is a plane perpendicular to the (002) plane of the graphite particle. That is, as shown in FIG. 3, the graphite particles (11) have a long, slender shape such that the length in the direction parallel to the layer plane is longer than the length in the direction perpendicular to the layer plane.

[0037] Here, the “orientation degree” of the graphite particle (11) is defined. The peak intensity originating from the (110) plane of the graphite particle (11) by powder X-ray diffraction measurement is denoted as PI1. Also, the peak intensity originating from the (002) plane is denoted as PI2. The peak intensity (PI1) originates from the ab-axis direction of the graphite crystal. The peak intensity (PI2) originates from the c-axis direction of the graphite crystal. Furthermore, the intensity ratio of the peak intensity (PI1) divided by the peak intensity (PI2) is defined as the orientation degree. That is, it is defined as “orientation degree = PI1 / PI2”.

[0038] The greater the degree of orientation, the more graphite particles (11) are oriented in the negative electrode composite layer (10) such that the c-axis is parallel to the negative electrode current collector (122) (the xy plane direction of Fig. 3). That is, the greater the degree of orientation, the higher the proportion of graphite particles (11) that are standing upright at an angle with respect to the surface of the negative electrode current collector (122).

[0039] And according to the inventors' research, it was found that when the magnetic field orientation described below is not performed, the degree of orientation of the main layer (10B) becomes less than 0.03. And it was found that by performing magnetic field orientation, the degree of orientation of the main layer (10B) can be made greater than 0.03. That is, it is possible to determine whether magnetic field orientation is being performed depending on whether the degree of orientation of the main layer (10B) is greater than 0.03.

[0040] In addition, the difference in orientation between the first graphite particle (11_1) and the second graphite particle (11_2) is explained. The second graphite particle (11_2) has a smaller median diameter than the first graphite particle (11_1). Therefore, the second graphite particle (11_2) has a smaller aspect ratio than the first graphite particle (11_1). That is, the second graphite particle (11_2) is closer to a sphere than the first graphite particle (11_1). Therefore, even when the same magnetic field is applied, the degree of orientation of the second graphite particle (11_2) is smaller than that of the first graphite particle (11_1). In other words, the second graphite particle (11_2) has a property that makes it difficult to be oriented in a magnetic field compared to the first graphite particle (11_1).

[0041] <Method for manufacturing secondary battery (1)>

[0042] Using the flowchart of FIG. 6 and the schematic diagrams of FIG. 7 to 10, a method for manufacturing the secondary battery (1) described above will be explained. In step S10, a first paste and a second paste are prepared (paste preparation process). The first paste is a paste containing first graphite particles (11_1). The second paste is a paste containing second graphite particles (11_2). The paste may be in the form of a slurry or an ink.

[0043] Using FIG. 7, an example of the preparation process for the first paste is described. The first graphite particles (11_1), binder (14), and conductive agent (15) are each supplied to a mixing machine (210) in predetermined amounts. A solvent is added to the materials supplied to the mixing machine (210), and the mixture is mixed. Accordingly, the first paste is completed. The mixing machine (210) may be of various types, and for example, a planetary mixer may be used. Likewise, in the preparation process for the second paste, a solvent is added to the second graphite particles (11_2), binder (14), and conductive agent (15), and the mixture is mixed using the mixing machine (210).

[0044] In steps S20-S50, a process of forming a negative electrode composite layer (10) on the first surface (122s1) of the negative electrode current collector (122) is performed. This is explained in detail using FIG. 8. In step S20, a first coating process is performed. In the first coating process, a first paste containing first graphite particles (11_1) is coated onto the surface of the negative electrode current collector (122). Specifically, the negative electrode current collector (122) is sent out at a constant speed in the conveying direction (T1) from a roll (122R) on which the negative electrode current collector (122) is wound. Then, the first paste is applied onto the negative electrode current collector (122) using a first coater (211). Accordingly, a first layer (L1) is formed. Various types of coaters can be used for the first coater (211). For example, the first coater (211) may be a slot die coater.

[0045] In step S30, a second coating process is performed. In the second coating process, a second paste containing second graphite particles (11_2) is coated onto the surface of the first layer (L1). Specifically, a second coater (212) is positioned downstream of the first coater (211) described above. Then, using the second coater (212), the second paste is applied onto the negative electrode current collector (122). Accordingly, a second layer (L2) is formed on the first layer (L1). Various types of coaters can be used for the second coater (212).

[0046] In step S40, an external magnetic field is applied to the first layer (L1) and the second layer (L2) (magnetic field orientation process). Specifically, a magnetic field generating means (221) is used to apply a magnetic field such that the direction of the magnetic field lines (MF) is approximately perpendicular to the surface of the negative current collector (122). The magnetic field generating means (221) may be a permanent magnet or an electromagnet, etc. Accordingly, the (002) plane of the first graphite particle (11_1) can be oriented so that it is approximately parallel to the direction of the magnetic field lines.

[0047] In step S50, the first layer (L1) and the second layer (L2) are dried (drying process). Specifically, they are dried by irradiating them with hot air (HA). Furthermore, the means used in the drying process are not limited to hot air, and drying by low-humidity air, vacuum, infrared rays, far-infrared rays, electron beams, etc., can be used alone or in combination. Through the drying process, the solvent can be removed from the first layer (L1) and the second layer (L2). Accordingly, a negative electrode composite layer (10) having a main layer (10B) and a surface layer (10A) can be formed on the first surface (122s1) of the negative electrode current collector (122).

[0048] In addition, the particle size distribution of graphite particles on the surface of the second layer (L2) after the drying process is the same as the particle size distribution of the surface layer (10A) described above (Fig. 4). That is, the particle size distribution of the second layer (L2) after drying has peaks at the first particle size (P1) and the second particle size (P2).

[0049] In steps S60-S90, a process of forming a negative electrode composite layer (10) on the second surface (122s2) of the negative electrode current collector (122) is performed. Additionally, since the contents of each step S60-S90 are identical to the contents of steps S20-S50 described above, the explanation is omitted. Accordingly, a negative electrode (114) is formed. The negative electrode (114) has a configuration in which a negative electrode composite layer (10) is disposed on both sides of the negative electrode current collector (122).

[0050] In step S100, the negative electrode (114) is pressed (press process). As shown in FIG. 9, for example, a roll press device (230) is used in the press process. The roll press device (230) is configured to roll the negative electrode (114) passing between a pair of rollers (231). Accordingly, the density and thickness of the negative electrode composite layer (10) can be adjusted.

[0051] In step S110, slit processing is performed. As shown in FIG. 9, in slit processing, the negative electrode (114) being sent in the feed direction (T1) is cut by a cutter (240). Accordingly, the width of the negative electrode (114) in the short length direction can be made to a width corresponding to the size of the secondary battery (1).

[0052] In step S120, an electrode body (108) is manufactured (electrode body manufacturing process). As shown in FIG. 2, in the electrode body manufacturing process, a positive electrode (112), a negative electrode (114), and a separator (116) are stacked so that the positive electrode (112) and the negative electrode (114) face each other with a separator (116) interposed. Specifically, the stack of the positive electrode (112) and the negative electrode (114) is wound.

[0053] In step S130, the electrode body (108) is pressed while being heated (heated press process). As shown in FIG. 10, for example, a flat plate press device (250) is used in the heated press process. Accordingly, the electrode body (108) can be compressed into a flat shape having a predetermined thickness. Additionally, the separator (116) can be attached. Furthermore, this heated press process may be performed after the electrolyte injection process (S150) described later.

[0054] In step S140, an electrode housing process is performed. Specifically, as shown in FIG. 1, a positive electrode terminal (104) and a negative electrode terminal (106) mounted on a cover plate (102b) are welded to each end of the electrode body (108). The electrode body (108) is housed inside the housing body (102a) through an opening (102c). After that, the housing body (102a) and the cover plate (102b) are joined together using laser welding or the like.

[0055] In step S150, a non-aqueous electrolyte is injected into the housing (102) through an injection port not shown (electrolyte injection process). Then, the injection port is hermetically sealed using a sealing member. By the above, the secondary battery (1) is completed.

[0056] Assignment

[0057] The problem is explained using the first comparative example of FIG. 11 and the second comparative example of FIG. 12. FIG. 11 and FIG. 12 are cross-sectional views similar to FIG. 3. The first comparative example ( FIG. 11) differs from the present embodiment ( FIG. 3) in that the negative electrode composite layer (310) is provided with only the first graphite particles (11_1) and magnetic field orientation is not performed on the negative electrode composite layer (310). In addition, the second comparative example ( FIG. 12) differs from the present embodiment ( FIG. 3) in that the negative electrode composite layer (410) is provided with only the first graphite particles (11_1). Magnetic field orientation is performed on the negative electrode composite layer (410) of the second comparative example.

[0058] In the negative electrode composite layer (310) of the first comparative example (Fig. 11), magnetic field orientation is not performed. Therefore, the layer surface (longer side) of the first graphite particle (11_1) is not oriented in a direction (z-direction) that is approximately perpendicular to the negative electrode current collector (122). Because of this, the path length (PL1) of the pores reaching from the separator (116) to the negative electrode current collector (122) increases. As a result, the curvature of the negative electrode composite layer (310) increases. Here, the curvature is the ratio of the path length (PL1) to the straight distance (SD) connecting the separator (116) to the negative electrode current collector (122). As the curvature increases, the absorption and release of Li ions between the layers of the first graphite particle (11_1) are not performed smoothly. Therefore, as the degree of curvature increases, the internal resistance of the secondary battery (1) increases, and the performance of the secondary battery (1) deteriorates.

[0059] Meanwhile, in the negative electrode composite layer (410) of the second comparative example (Fig. 12), magnetic field orientation is performed. Accordingly, the layer surface (longer length surface) of the first graphite particle (11_1) is oriented in a direction (z-direction) that is approximately perpendicular to the negative electrode current collector (122). Because of this, the path length (PL2) of the pores in the second comparative example can be made shorter than the path length (PL1) of the pores in the first comparative example. Therefore, in the second comparative example, the curvature is smaller than in the first comparative example, so the internal resistance can be reduced. However, when the first graphite particle (11_1) is magnetically oriented, the angle formed between the layer surface of the first graphite particle (11_1) and the surface of the negative electrode current collector (122) becomes larger. Accordingly, the pointed tip surface ((110) surface) of the first graphite particle (11_1) ends up protruding upward from the surface of the negative electrode composite layer (410) (see region (A2)). As a result, the surface roughness (Ra2) of the negative electrode composite layer (410) of the second comparative example becomes larger than the surface roughness (Ra1) of the negative electrode composite layer (310) of the first comparative example. There is a risk that the adhesion between the surface of the negative electrode composite layer that is magnetically oriented and the separator (116) will deteriorate compared to the adhesion between the surface of the negative electrode composite layer that is magnetically oriented and the separator (116).

[0060] In addition, various indicators can be used for surface roughness (Ra1 and Ra2). In this embodiment, arithmetic mean roughness is used as the surface roughness. Arithmetic mean roughness can be measured in accordance with the JIS B 0601:2001 standard. The same applies to the surface roughness Ra0 described below.

[0061] <Effect>

[0062] In the negative electrode composite layer (10) of the present embodiment (Fig. 3), the orientation degree of the main layer (10B) is 0.03 or higher. That is, the main layer (10B) is oriented in a magnetic field. Therefore, since the curvature of the main layer (10B) is small, the internal resistance can be reduced. Also, the particle size distribution of the graphite particles (11) included in the surface layer (10A) has a peak at the second particle size (P2) in addition to the first particle size (P1). That is, in the surface layer (10A), there exists a first graphite particle (11_1) having a peak at the first particle size (P1) and a second graphite particle (11_2) having a peak at the second particle size (P2). In other words, the surface layer (10A) has a mixture of large first graphite particles (11_1) and small second graphite particles (11_2). Accordingly, it is possible to create a state in which the small second graphite particles (11_2) are filled in the gaps between the pointed tip surfaces of the large first graphite particles (11_1) (refer to region (A0)). By filling the concave areas formed between the tip surfaces of the first graphite particles (11_1) with the second graphite particles (11_2), the surface roughness (Ra0) of the surface layer (10A) can be reduced. Therefore, it is possible to improve the adhesion between the surface layer (10A) and the separator (116).

[0063] In the process of forming the negative electrode composite layer (10) of the present embodiment, a magnetic field orientation process (step S40) is performed after the application of the first layer (L1) (step S20) and the application of the second layer (L2) (step S30), and before the drying process (step S50). Accordingly, the first layer (L1) and the second layer (L2) can be magnetically oriented while in a fluid state. As described above, the second graphite particle (11_2) has a property that makes it more difficult to be magnetically oriented than the first graphite particle (11_1). Therefore, by applying a magnetic field to the first layer (L1) and the second layer (L2), the first graphite particle (11_1) contained in the first layer (L1) can be selectively magnetically oriented. As the first graphite particles (11_1) are oriented in a magnetic field, a concave portion is formed between the leading surfaces of the first graphite particles (11_1). By moving the second graphite particles (11_2), which are not oriented in a magnetic field, into this concave portion, the surface roughness can be reduced. Subsequently, by performing a drying process, a surface layer (10A) having a small surface roughness (Ra0) can be formed (see FIG. 3).

[0064] Although embodiments have been described in detail above, they are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations of the specific embodiments exemplified above. The technical elements described in this specification or drawings exhibit technical utility either individually or in various combinations, and are not limited to the combinations described in the claims at the time of filing. Furthermore, the technology exemplified in this specification or drawings achieves multiple objectives simultaneously, and possesses technical utility in itself by achieving one of those objectives. Explanation of the symbols

[0065] 1: Secondary battery 10: Poison composite layer 10A: Surface layer 10B: Main floor 11: Graphite particles 13: Adhesive layer 112: Straight Drama 114: Buguk 116: Separator 122: Buguk entire house P1: First particle size P2: Second particle size

Claims

Claim 1 A secondary battery having a positive electrode and a negative electrode facing each other via a separator, wherein the negative electrode comprises a negative electrode current collector, a negative electrode composite layer provided on the negative electrode current collector and containing graphite particles, and an adhesive layer provided between the surface of the negative electrode composite layer and the separator, wherein the negative electrode composite layer comprises a surface layer in contact with the adhesive layer and a main layer located between the surface layer and the negative electrode current collector, wherein in the XRD profile of the main layer, the degree of orientation, which is the intensity ratio of the (110) plane of the graphite crystal divided by the intensity of the (002) plane, is 0.03 or greater, the particle size distribution of the graphite particles included in the surface layer has a first particle size and a second particle size smaller than the first particle size, and the particle size distribution of the graphite particles included in the main layer has a peak at the first particle size and does not have a peak at the second particle size. Claim 2 A secondary battery according to claim 1, wherein the particle size distribution of graphite particles on the surface of the negative electrode composite layer has peaks at the first particle size and the second particle size. Claim 3 A method for manufacturing a secondary battery in which a positive electrode and a negative electrode face each other via a separator, comprising: a first coating process in which a first paste containing first graphite particles having a peak at a first particle size is coated on the surface of a negative electrode current collector to form a first layer; a second coating process in which a second paste containing second graphite particles having a peak at a second particle size smaller than the first particle size is coated on the surface of the first layer to form a second layer; a magnetic field alignment process in which an external magnetic field is applied to the first layer and the second layer; and a drying process in which the first layer and the second layer are dried after the magnetic field alignment process. Claim 4 A method for manufacturing a secondary battery according to claim 3, wherein the particle size distribution of graphite particles on the surface of the second layer after the drying process has peaks at the first particle size and the second particle size. Claim 5 A method for manufacturing a secondary battery according to claim 3, wherein the median diameter of the first graphite particle is larger than the median diameter of the second graphite particle. Claim 6 A method for manufacturing a secondary battery according to claim 5, wherein the median diameter of the first graphite particle is within the range of 15 to 40 micrometers, and the median diameter of the second graphite particle is within the range of 5 to 20 micrometers.